2005
DOI: 10.1038/sj.ejcn.1602335
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for goiter in primary school girls in Qom city of Iran

Abstract: Objective: Goiter is endemic in Iran. The iodine deficiency disorders program was begun a few years ago in Iran, and the coverage of iodized salt is sufficient now. But, in a periodic yearly medical examination of primary school girls in Qom, the prevalence of goiter was above 30% in 2002. This survey was designed to study the risk factors of goiter in those students. Design: The study was a randomized (multistage, proportional simple random sampling) case-control study. Subjects and interventions: We selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
(15 reference statements)
2
9
1
Order By: Relevance
“…This report is in line with previous findings elsewhere [6, 17, 23, 24, 26, 35, 36, 41, 42]. This might be due to a higher iodine requirement of females to support their growth and development [35].…”
Section: Discussionsupporting
confidence: 92%
“…This report is in line with previous findings elsewhere [6, 17, 23, 24, 26, 35, 36, 41, 42]. This might be due to a higher iodine requirement of females to support their growth and development [35].…”
Section: Discussionsupporting
confidence: 92%
“…For example, as early as 1952, France introduced an iodine fortification program on a voluntary basis, but most French people are still living in a mildly to moderately iodine-deficient environment, and a nationwide study of adults demonstrated that higher education was related to a higher iodine intake (36). Similar findings were reported from South Africa (37) and Iran (38), where higher socioeconomic status was associated with more frequent use of iodized salt, higher urinary iodine excretion levels, and lower goiter risk. Likewise, a study from Madrid, Spain, demonstrated that children of less educated mothers had a lower iodine intake than children of better educated mothers (39).…”
Section: Discussionsupporting
confidence: 72%
“…Storing the salt in a container with lid was significantly associated with higher iodine content. Storage of salt in open containers was reported as a risk factor in a study from Iran [40]. …”
Section: Discussionmentioning
confidence: 99%